Impact of crop diversification on rural poverty in Nepal - Thapa, Ganesh; Kumar, Anjani; Roy, Devesh; Joshi, Pramod Kumar (Wiley, 2018)
Crop diversification into high‐value crops (HVCs) can be an important strategy to augment income, generate employment, and reduce poverty in developing countries. We study the impact of crop diversification (share of production value obtained from the HVCs) on household (HH) welfare measures in Nepal. We use three rounds of the nationally representative Nepal Living Standard Surveys: NLSS I (1994/95), NLSS II (2004/05), and NLSS III (2010/11). The dose–response function, propensity score matching, and instrumental variable techniques are used to estimate the impact of crop diversification. Results show the positive impact of HVCs on the monthly per capita consumption expenditure and poverty outcomes. Among HVCs growers, HHs growing vegetables have the better welfare outcomes. While establishing the relationship between degree of agricultural diversity and poverty measures, we find that the marginal farmers need to at least derive 35% of the share of revenue from HVCs to escape from poverty.